Strontium-substituted apatite coating grown on Ti6Al4V substrate through biomimetic synthesis - Oliveira, A. L. (2007)
During the last few years Strontium has been shown to have beneficial effects when incorporated at certain doses in bone by stimulating bone formation. It is believed that its presence locally at the interface between an implant and bone will enhance osteointegration and therefore, ensure the longevity of a joint prosthesis. In this study we explore the possibility of incorporating Sr into nano-apatite coatings prepared by a solution-derived process according to an established biomimetic methodology for coating titanium based implants. The way this element is incorporated in the apatite structure and its effects on the stereochemistry and morphology of the resulting apatite layers was investigated, as well as its effect in the mineralization kinetics. By using the present methodology it was possible to incorporate increasing amounts of Sr in the apatite layers. Sr was found to incorporate in the apatite layer through a substitution mechanism by replacing Ca in the apatite lattice. The presence of Sr in solution induced an inhibitory effect on mineralization, leading to a decrease in the thickness of the mineral layers. The obtained Sr-substituted biomimetic coatings presented a bone-like structure similar to the one found in the human bone and therefore, are expected to enhance bone formation and osteointegration.